Hasil Belajar Kewirausahaan Ditinjau Dari Aspek Motivasi Dan Konsep Diri - Ira Pratiwi Ramdayana; Memmy Jayanti; Siti Muharomah (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The aim of this research is to determine 1). The influence of learning motivation and self-concept together on the entrepreneurship learning outcomes of class XI students at Pertiwi Vocational School, 2). The influence of learning motivation on the entrepreneurship learning outcomes of class The sample used was 60 students as research samples using simple random sampling techniques with multiple linear regression. Based on the results of the hypothesis and data analysis, it is concluded as follows: 1). There is a significant influence of motivation and self-concept together on the entrepreneurship learning outcomes of class XI students at Pertiwi Vocational School. This is proven by the simultaneous test results obtained by the calculated f value of 34.333 > f table 2.76. 2) There is a significant influence of motivation on the entrepreneurship learning outcomes of class XI students at Pertiwi Vocational School. This is proven by the partial test results which obtained a calculated t value of 4.125 > t table 1.672 3) There is a significant influence of self-concept on the entrepreneurship learning outcomes of class XI students at Pertiwi Vocational School. This is proven by the partial test results which obtained a calculated t value of 2.065 > t table 1.672.